Epistemological Deconstruction Of Syarafuddin Al-Musawi On The Authority Of Abu Hurairah’s Hadith In Contemporary Hadith Studies - Irfan Harmoko (AL QUDS : Jurnal Studi Alquran dan Hadis, 2026)
This article analyzes Syarafuddin al-Musawi’s criticism of the authority of the hadith narrated by Abu Hurairah by focusing on the problem of the epistemological validity of hadith criticism in contemporary hadith studies. This research departs from the lack of systematic mapping of the basis of al-Musawi’s argumentation and from the limitations of previous studies, which tend to situate his criticism solely within the framework of Sunni-Shia polemics without critically examining its methodological construction. The research aims to identify al-Musawi’s argumentation patterns, evaluate its evidence base, and assess its contribution to the development of modern hadith studies. This research uses a qualitative method based on literature studies with a historical-critical approach and critical hermeneutics. The primary source of research is al-Musawi’s works on Abu Hurairah, while secondary sources include classical hadith literature, rijal books, and contemporary academic studies. The data was analyzed through three stages: classification of the theme of criticism, comparison with classical hadith sources, and historical evaluation of the socio-political context of the hadith narration. The results of the study show that al-Musawi’s criticism is divided into three main aspects, namely biographical criticism of Abu Hurairah’s credibility, quantitative criticism of the number of hadiths narrated, and socio-historical criticism of the relationship between hadith authority and political patronage in the early days of Islam. This study also found that al-Musawi’s argument makes an important contribution to opening up a space for critical reading of the construction of hadith-narration authority, especially through the use of historical and socio-political approaches. However, some of his arguments remain indicative, as they are not fully supported by comprehensive sanad verification and adequate historical evidence of the direct relationship between political power and the production of hadith history. This article concludes that al-Musawi’s criticism does not represent a total rejection of Abu Hurairah, but rather an attempt to reconstruct the study of hadith to be more open to multidisciplinary approaches and historical-critical evaluation.